HEC/PVDF coated glass substrate for acetone liquid sensor - Jali, Mohd Hafiz; Jahava, Marlina; Ahmad Zamzuri, Ahmad Nur Azeim; Md Johari, Md Ashadi; Ahmad, Aminah; Mohd Yusof, Haziezol Helmi; Adnan Zain, Huda; Harun, Sulaiman Wadi; Yasin, Moh (National Institute of Optoelectronics, 2023)
An acetone liquid sensor has been successfully demonstrated by utilizing glass substrate coated with Hydroxyethylcellulose/Polyvinylidene Fluoride (HEC/PVDF). The sensing mechanism is based on the change in refractive index (RI) of the HEC/PVDF coating layer when exposed to acetone concentration variations. When the light progress through the sensing material, the intensity decrease due to absorption and scattering. The proposed sensor's produces exceptional results where output voltage has decreased linearly from 1.8 V to 1.3 V. It showed a good response with sensitivity of 0.0331 V/% and a linearity of 99.1 % as compared to an uncoated glass substrate.